IMPLEMENTATION OF COURSE REVIEW HORAY LEARNING MODEL IN SCIENCE SUBJECTS IN GRADE IV OF SD NEGERI BANGUNREJO - Aulia Citra; Dian Samitra; Tio Gusti Satria (Widyagogik, 2021)
This thesis aims to know the completed learning results of students after the study model of Course Review Horay applied to the science subjects of grade IV SD Negeri Bangunrejo. The research method used by quasy-experiment. Data collection techniques in research use tests and interviews. Data analysis techniques with steps: average score and standard deviation, normality test and z test. The results showed the results of studying the IPA of grade IV students of SD Negeri Bangunrejo after the Course Review Horay model was significantly completed.